Progress on the Classification, Characteristics and Food Industry Application of Microbial Proteases and Lipases - Yao ZHANG; Jiaxin WANG; Chanchan WEN; Jiayun HU; Xiaofeng LIU; Yuanfeng WU (Shipin gongye ke-ji)
Proteases and lipases are two major kinds of industrial hydrolysis enzymes and widely used in various food industry (e.g., cheese making, soy sauce fermentation, liquor brewing, meat tenderization, etc.). Proteases and lipases are mainly obtained from animals, plants and microorganisms. The microbial proteases and lipases have attracted great interest due to easy obtaining, low cost and simple molecular modification. Currently, there is a significant amount of research on microbial proteases and lipases, including strain selection from different sources, optimization of enzyme production, physicochemical characteristics and molecular modification of enzyme for better application in food processing. This article summarizes the relevant research on microbial proteases and lipases. This elucidates the classification and characteristics of microbial proteases (serine protease, cysteine protease, aspartic protease and metalloprotease) and lipases, as well as their application in the food industry (e.g., meat, baking, milk, bean, liquor, tea, etc.). This paper provides a theoretical reference to fully understand the applicability of various microbial proteases and lipases, improve their utilization efficiency and promote their application in food industry.